Deviance management: insiders, outsiders, hiders, and drifters - Bader, Christopher D. (University of California Press, 2019)
Introduction : insiders, outsiders, hiders, and drifters -- The complementarity of deviance and conformity -- Deviance and conformity : the pressure of dual identities -- Fighting for normal? -- Bigfoot : undiscovered primate or inter-dimensional spirit? -- Sexuality and gender identity : assimilation vs. liberation -- Insiders and the normalization of illegal drugs -- Conclusion : studying deviance management -- Appendix 1 : on applying the theory of deviance management -- Appendix 2 : supplemental data analyses.